2017
DOI: 10.1039/c6ra24852g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced p-cresol photodegradation over BiOBr/Bi2O3 in the presence of rhodamine B

Abstract: Bismuth oxide is a visible-light activated photocatalyst that is adversely affected by a high rate of electronhole recombination. To mitigate this, BiOBr/Bi 2 O 3 composites were synthesized where BiOBr formed submicron thick platelets at the surface of the Bi 2 O 3 particles. XRD measurements show the preferential formation of a (110)-facetted BiOBr overlayer which can be attributed to the commensurate structure of this plane with the (120) plane of Bi 2 O 3 . The photodegradation of p-cresol and RhB was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The calculations show that the E g of the pristine A has a similar value as the one conventionally obtained for Ag 2 CrO 4 when it is synthesized by the coprecipitation method, the pristine B shows an E g value that corresponds to a combination of the one for α-Bi 2 O 3 and Bi 2 O 2 CO 3 , 2.80 and 3.42 eV, respectively, , and in the case of the mixtures, no E g entirely match those values belonging to the pristine A or B, which indicates that the grinding process effectively allows the formation of heterojunctions between the composing semiconductors.…”
Section: Results and Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The calculations show that the E g of the pristine A has a similar value as the one conventionally obtained for Ag 2 CrO 4 when it is synthesized by the coprecipitation method, the pristine B shows an E g value that corresponds to a combination of the one for α-Bi 2 O 3 and Bi 2 O 2 CO 3 , 2.80 and 3.42 eV, respectively, , and in the case of the mixtures, no E g entirely match those values belonging to the pristine A or B, which indicates that the grinding process effectively allows the formation of heterojunctions between the composing semiconductors.…”
Section: Results and Discussionsupporting
confidence: 49%
“…Besides, because these semiconductors are characterized by absorption spectra governed mainly by indirect allowed electronic transitions, the optical band gap (E g ) was extracted from the Kubelka−Munk equation αhν = C(hν − E g ) 2 , where α represents the absorption coefficient, hν is the photon energy, and C is a proportionality constant. 42 The calculations show that the E g of the pristine A has a similar value as the one conventionally obtained for Ag 2 CrO 4 when it is synthesized by the coprecipitation method, 42 the pristine B shows an E g value that corresponds to a combination of the one for α-Bi 2 O 3 and Bi 2 O 2 CO 3 , 2.80 and 3.42 eV, respectively, 43,44 and in the case of the mixtures, no E g entirely match those values belonging to the pristine A or B, which indicates that the grinding process effectively allows the formation of heterojunctions between the composing semiconductors.…”
Section: ■ Results and Discussionmentioning
confidence: 53%
“…On the other hand, Au-ZnO NRs showed a six-fold increase of AQY over bare ZnO NRs in the visible region, which can be attributed to the plasmonic effect of Au. In addition, the BiOBr/Bi 2 O 3 heterostructures were demonstrated for photodegradation of an RhB/p-cresol mixture [45]. The SEM image showed that the composites comprised BiOBr platelets arranging in whorls perpendicular to the Bi 2 O 3 surface (Figure 4c).…”
Section: Quantum Yield Of Photodegradationmentioning
confidence: 96%
“…Recent developments of semiconductor BiOBr as photocatalyst for wastewater treatment have attracted much attention. [1,2] It was demonstrated in a number of studies that composite metallic oxide/BiOBr semiconductor photocatalysts produced an evident improvement in a series of photocatalytic reaction rates in contrast to pure BiOBr semiconductor counterparts, such as Bi 2 O 3 , [3] ZnO, [4] TiO 2 , [5] Fe 3 O 4 , [6] and WO 3 , [7] have proven to be effective counterparts in fabricating heterojunctions with BiOBr, all of which have shown excellent photocatalytic properties under visible light. However, there are relatively few studies devoted to SnO 2 in the preparation of heterojunctions with BiOBr.…”
Section: Introductionmentioning
confidence: 99%